A “State-Villaine Must Be Like The Winde, / That Flies Unseene Yet Lifts An Ocean”: Machiavellian Italian and Turk in John Mason’s "The Turke" - Sıla ŞENLEN GÜVENÇ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
Machiavelli’s political philosophy emphasizing leadership qualities, a sense of practical politics, and the intellect to attain and maintain power at all costs, has been greatly influential in 16th and 17th century English drama. In accordance with this philosophy, as expressed in Machiavelli’s Prince and Discourses, the stage Machiavellian, as exhibited by characters ranging from Marlowe’s Tamburlaine to Shakespeare’s Edmund and Richard III, is intelligent, persuasive, conniving, opportunist and inclined to violence. A Jacobean play that incorporates two types of Machiavellians is John Mason’s An Excellent Tragedy of Mulleasses the Turke, and Borgias Governour of Florence (1607); Borgias –an Italian and Mulleasses –a Turk. It is not surprising to see such Machiavellians on the Renaissance stage, but the representation of these particular characters side by side is noteworthy. The majority of the Renaissance English plays represent foreigners according to their position with respect to England and Christianity. Thus, there are differences of representation between Christian and non-Christian foreigners. Generally, Turks –a term that applied to indicate Seljuks Turks, ‘Othomans’, Moors, Arabs, Greeks, Persians or any nation in the boundaries of the Orient in early modern period- in English drama were allegorical figures symbolizing the Orient, the East or Islam. They were compared and contrasted with Christians in order to define Englishness and illustrate the ‘superiority’ of their culture/religion. But in the Turke, the Christian Italian is as cruel and devious as the Muslim Turk. Thus, he represents the Roman Catholic Church instead of Christianity. Since England officially broke off with the Catholic Church in the mid-sixteenth century,Catholicism appears to be as much a threat to England as the ‘Mohammedans’ chiefly represented by the Ottoman Turk. The aim of this paper is to examine these two particular Machiavellian characters in Mason’s “tragedy of blood” in relation to their sources and popular notions about them to show that England feared the return to Catholicism as much as the Ottoman threat.